Analysis of thermal effects in end-diode-pumped, Q-switched Nd:YVO4 laser - Kaskow, Mateusz; Boruc, Lech; Boruc, Lukasz; Giemza, Maciej; Piasecki, Michal (Photonics Letters of Poland, 2013)
We present a laboratory model of a Q-switched Nd:YVO4 laser with thermal effects compensation dedicated as a laser head for marking devices. Theoretical analysis on thermal effects were performed and resonator parameters were optimized. For 10 kHz repetition rate we obtained about 0.25 mJ of pulse energy corresponding to about 45 kW of peak power with slope efficiency 14%. M2 parameter was 1.6. Full Text: PDF References J. E. Geusic, H. M. Marcos, L. G. Van Uitert, "Laser oscillations in nd-doped yttrium aluminum, yttrium gallium and gadolinium garnets", Applied Physics Letters 4 (10), (1964) CrossRef L. Gorajek, L. Galecki, "Tunable, gain switched Ti3+:Al2O3 laser pumped by intracavity frequency doubled Nd3+:YLF laser", Photonics Letters of Poland 1, No 3, 136-138 (2009) CrossRef W. Zendzian, J. K. Jabczynski, P. Wachulak, J. Kwiatkowski, "High-repetition-rate, intracavity-pumped KTP OPO at 1572 nm", Appl. Phys. B 80, 329-332 (2005) CrossRef J. Swiderski, A. Zajac, P. Konieczny, M. Skorczakowski, "Numerical model of a Q-switched double-clad fiber laser", Opt. Express 12, 3554-3559 (2004) CrossRef J. Swiderski, A. Zajac, P. Konieczny, M. Skorczakowski, "Q-switched Nd-doped double-clad fiber laser", Opto-Electronics Review, vol. 13, no. 3, 29-33, 2005 DirectLink